2020
DOI: 10.1038/s41467-020-17151-2
|View full text |Cite
|
Sign up to set email alerts
|

The RNA quality control pathway nonsense-mediated mRNA decay targets cellular and viral RNAs to restrict KSHV

Abstract: Nonsense-mediated mRNA decay (NMD) is an evolutionarily conserved RNA decay mechanism that has emerged as a potent cell-intrinsic restriction mechanism of retroviruses and positive-strand RNA viruses. However, whether NMD is capable of restricting DNA viruses is not known. The DNA virus Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiological agent of Kaposi's sarcoma and primary effusion lymphoma (PEL). Here, we demonstrate that NMD restricts KSHV lytic reactivation. Leveraging high-throughput transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 70 publications
2
36
0
Order By: Relevance
“…Our results also indicated that the NMD-mediated degradation of EBV BRLF1-encoding transcripts depends on the presence of introns as well as the long 3′ UTR. Our results are consistent with the findings by Zhao and colleagues who recently reported that the 3′ UTR of KSHV Orf50 transcripts is recognized by the NMD machinery in an intron-dependent manner, and that, consequently, silencing of the NMD components UPF1 or UPF3X resulted in de-repression of KSHV reactivation [ 51 ]. The conservation of these NMD-inducing features in the transactivator locus of EBV and KSHV may suggest that these viruses have adopted NMD-mediated regulation of viral gene expression and reactivation as an integral part of their life cycle.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also indicated that the NMD-mediated degradation of EBV BRLF1-encoding transcripts depends on the presence of introns as well as the long 3′ UTR. Our results are consistent with the findings by Zhao and colleagues who recently reported that the 3′ UTR of KSHV Orf50 transcripts is recognized by the NMD machinery in an intron-dependent manner, and that, consequently, silencing of the NMD components UPF1 or UPF3X resulted in de-repression of KSHV reactivation [ 51 ]. The conservation of these NMD-inducing features in the transactivator locus of EBV and KSHV may suggest that these viruses have adopted NMD-mediated regulation of viral gene expression and reactivation as an integral part of their life cycle.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the Gene Set Enrichment Analysis (GSEA) of UPF1-associated cellular transcripts showed that 14 gene sets were significantly enriched with UPF1 or phospho-UPF1 in EBV-infected cells, suggesting that NMD may also modulate the activity of several cellular processes during infection ( S8 Fig ). It will be interesting to determine the extent to which NMD-mediated control of these pathways regulates EBV and KSHV reactivation, especially because some of these pathways have previously been implicated in the regulation of EBV and/or KSHV reactivation; these include the unfolded protein response, whose regulation by NMD was recently shown to affect KSHV reactivation [ 51 ] and the MYC pathway that was recently reported to suppress EBV reactivation [ 52 ]. In view of this, it seems plausible that EBV and KSHV have evolved mechanisms to manipulate NMD-mediated transcript degradation.…”
Section: Discussionmentioning
confidence: 99%
“…For transcriptional regulation, we found enrichment of gene set for nonsense-mediated mRNA decay (NMD) which is a universally conserved RNA quality control process [40] . Interaction of RNA binding proteins at 3′ untranslated regions (UTRs) and initiation factors at the 5′ end further influence mRNA translation.…”
Section: Resultsmentioning
confidence: 99%
“…Nonsense-mediated mRNA decay (NMD) is an RNA quality control implemented by the cells to restrict the action of the RNA viruses and serve cellular quality control. Interestingly, viral RTA' mRNA is targeted by NMD, impeding KSHV lytic reactivation in PEL cells (Zhao et al, 2020). However, KSHV has evolved to overcome some of these quality controls and exonuclease activities by circularizing its structural and regulatory RNAs incorporated into the virions (Abere et al, 2020).…”
Section: Manipulation Of the Cell Cyclementioning
confidence: 99%